Experimental NMR and MS study of benzoylguanidines. Investigation of E/Z isomerism - Santo, Rafael Dias Do Espírito [UNESP]; Simas, Rosineide Costa; Magalhães, Alviclér; Santos, Vanessa Gonçalves Dos; Regiani, Thais; Isler, Ana Cristina; Martins, Natiza Graziele [UNESP]; Eberlin, Marcos Nogueira; González, Eduardo René Pérez [UNESP] (Wiley, 2013)
Molecules containing the guanidinic nuclei possess several pharmacological applications, and knowing the preferred isomers of a potential drug is important to understand the way it operates pharmacologically. Benzoylguanidines were synthesized in satisfactory to good yields and characterized by NMR, Electrospray Ionization Mass Spectrometry (ESI-MS) and Fourrier Transform InfraRed Spectroscopy techniques (FTIR). E/Z isomerism of the guanidines was studied and confirmed by NMR analysis in solution (1H-13C Heteronuclear Single Quantum Coherence (HSQC) and Heteronuclear Multiple-Bond Correlation (HMBC), 1H-15N HMBC, 1H- 1H Correlation Spectroscopy (COSY) and Nuclear Overhauser Effect Spectroscopy (NOESY) experiments) at low temperatures. Compounds with p-Cl and p-Br aniline moiety exist mainly as Z isomer with a small proportion of E isomer, whereas compounds with p-NO2 moiety showed a decrease in proportion of isomer Z. The results are important for the application of these molecules as enzymatic inhibitors. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: benzoylguanidines; E/Z isomerism; ESI-MS characterization; NMR experiments; Correlation spectroscopy; Electrospray ionization mass spectrometry; Heteronuclear single-quantum coherences; Nuclear overhauser effect spectroscopy; Transform infrared spectroscopy; Bromine compounds; Chlorine compounds; Fourier transform infrared spectroscopy; Mass spectrometry; Molecules; Nitrogen compounds; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Quantum theory; Stereochemistry; Isomers